2017
DOI: 10.1038/hortres.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

An eFP browser for visualizing strawberry fruit and flower transcriptomes

Abstract: Wild strawberry Fragaria vesca is emerging as an important model system for the cultivated strawberry due to its diploid genome and availability of extensive transcriptome data and a range of molecular genetic tools. Being able to better utilize these tools, especially the transcriptome data, will greatly facilitate research progress in strawberry and other Rosaceae fruit crops. The electronic fluorescent pictograph (eFP) software is a useful and popular tool to display transcriptome data visually, and is wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 21 publications
(53 reference statements)
3
65
0
Order By: Relevance
“…Examination of RNA-seq data of diploid strawberry showed that the FveARF8 gene is expressed at a high level in floral organs and fruit, and it is also moderately expressed in seedlings ( Figure S5F; Hawkins et al, 2017). This broad expression pattern of FveARF8 suggests that FveARF8 may repress auxin signalling in many tissues and developmental stages.…”
Section: Mutations In Fvetaa1mentioning
confidence: 98%
See 2 more Smart Citations
“…Examination of RNA-seq data of diploid strawberry showed that the FveARF8 gene is expressed at a high level in floral organs and fruit, and it is also moderately expressed in seedlings ( Figure S5F; Hawkins et al, 2017). This broad expression pattern of FveARF8 suggests that FveARF8 may repress auxin signalling in many tissues and developmental stages.…”
Section: Mutations In Fvetaa1mentioning
confidence: 98%
“…Surprisingly, the young plants derived from T0 mother plant (T0-11) all looked similar to one another ( Figure 4a) despite that some young plants were homozygous for À1a deletion in FveTAA1. Examination of RNA-seq data revealed that FveTAA1 was only expressed at late-stage anther ( Figure S5E; Hawkins et al, 2017;Hollender et al, 2014). Therefore, TAA1 may not play a role in seedling development.…”
Section: Inheritance and Stability Of Crispr-induced Mutations In Thementioning
confidence: 99%
See 1 more Smart Citation
“…The most obvious phenomenon during fruit ripening is the synthesis of anthocyanins. Previous transcriptome analysis revealed that flavonoids biosynthesis genes were induced transcription in the receptacle, implicating the importance of these genes 24 . The grey60 color module (Table S6) is correlated with the octoploid receptacle development, and the correlation is getting higher as the receptacle matures (Figure 3c).…”
Section: Resultsmentioning
confidence: 99%
“…We collected total 80 Illumina-based datasets representing 36 different fruit tissues of diploid and octoploid fruit at different developmental stages, including seven development stages for diploid receptacle (cortex and pith) and other fruit tissues (wall, style, embryo, ovule, ghost) 23,24 . as well as the four development stages (green, white, turning, red) for octoploid achene and receptacle 25 .…”
Section: Methodsmentioning
confidence: 99%